A Comparative Study of Basic Health Services Provided in Government and Private Schools of Bhopal City - Jamra, Vishal; Bankwar, Vishal; Saxena, Dinesh M. (National Journal of Community Medicine, 2014)
Background & Objectives: School health services play an important role to address the health needs of children. It ensures good current and future health and improves educational outcomes by increasing enrolment. But these are one of the most neglected services due to lack of awareness.A comparative study of basic health services provided in schools was conducted to find out the attitude of teachers in providing these services and imparting health education. Material and methods: A cross sectional observational study was carried out in 5 government schools and 5 private schools in Bhopal city. Results: None of the schools had a medical officer. Health of children was assessed at the time of admission in only 20% of the schools. Periodic health checkups were done in 80% government schools and 100% of private schools. Health record was maintained in 60% government and 40% private schools. Deficiencies were also noted in availability of nutritious food in school premises, per capita classroom space, student teacher ratio, lavatories and safe drinking water. Heath education as a subject was included in only 1 private school. Conclusion: Most of the schools are lacking in services related to health of children and there is dire need to improve the condition in both government and private sector.